Chemoenzymatic collective synthesis of optically active hydroxyl(methyl)tetrahydronaphthalene-based bioactive terpenoids - Batwal, Ramesh U.; N. P. Argade (Organic & Biomolecular Chemistry, 2015)
Starting from succinic anhydride and 2-methylanisole, a chemoenzymatic collective formal/total synthesis of several optically active tetrahydronaphthalene based bioactive natural products has been presented via advanced level common precursors; the natural product and antipode (-)/(+)-aristelegone B. Regioselective benzylic oxidations, stereoselective introduction of hydroxyl groups at the alpha-position of ketone moiety in syn-orientation, efficient enzymatic resolutions with high enantiomeric purity, stereoselective reductions, samarium iodide induced deoxygenations and tandem acylation-Wittig reactions without racemization and/or eliminative aromatization were the key features. An attempted diastereo-selective synthesis of (+/-)-vallapin has also been described.